Design for additive manufacturing and finite element analysis for high flexion total knee replacement (TKR) / Solehuddin Shuib …[et al.] - Shuib, Solehuddin; Azemi, Mohammad Arsyad; Mohd Arrif, Iffa; Hamizan, Najwa Syakirah (Universiti Teknologi MARA, 2021)
The patient from the Asian region always demanded a fully functional knee implant, which implied a high-flexion range of motion. Most of their daily life activities utilized the deep knee flexion which flexed until 165° such as the Japanese proper sitting style and Muslim prayer position. The problem of the study is extending the range of motion or achieving the high flexion of total knee replacement as the traditional total knee replacement was incapable to achieve more than 115°. Hence, the purpose of this study is to achieve a modified design of a knee implant that can flex up to 165° by carried out a static structural analysis in the ANSYS R16. There are 0°, 90°, 135°, and 165° angles of flexion with a different net force based on the percentage of body weight implemented on the knee implant. The analysis includes total deformation, Von Mises stress, shear stress, and contact pressure on knee implant were observed and compared to find better modification design. The total deformation had been decreased by about 69% at 0° flexion, 58.5% at 90° flexion, 90.93% at 135° flexion. The contact pressure also had been decreased by about 99.2%, 22.2%, 99.98% at angle flexion of 0, 90, and 135, respectively. The same declination happened to von Mises stress at about 85.05%, 9.52%, and 88.04% at the same angle of 0, 90, and 135, respectively.